PENGARUH REALISTIC MATHEMATICS EDUCATION BERBANTUAN ETHMAS QR-CODE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Ade Nasicha Balqiz; Ratri Rahayu; Himmatul Ulya (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2025)
Mathematical problem-solving skills are important to help learners apply mathematical concepts in everyday life. The mathematical problem-solving abilities of students at SMP Negeri 1 Bae Kudus are still considered low, as evidenced by the preliminary study results on the VII-B class students with an average score of 37.34. Based on these findings, this study aims to improve the mathematical problem-solving abilities of seventh-grade students thru the application of the Realistic Mathematics Education (RME) learning model assisted by Ethmas QR-Code media. This research uses a quantitative approach with a quasi-experimental design, where class VII-B is designated as the experimental group and class VII-A as the control group. The selection of the sample was conducted using the simple random sampling technique. The study population consisted of 256 students, with a sample of 2 classes comprising 64 students. Initial data analysis includes normality tests, homogeneity tests, and mean equality tests, while final data analysis involves independent two-sample t-tests, N-Gain calculations, and independent two-sample t-tests. The instrument used in this study is a test to measure students' mathematical problem-solving abilities. The results of this study indicate that: (1) The average mathematical problem-solving ability of students taught using the RME learning model with Ethmas QR-Code learning media is better compared to the average using the direct learning model. (2) There is a significant improvement in mathematical problem-solving abilities before and after the implementation of the RME model aided by Ethmas QR-Code media, with a high category of improvement. Further research is needed to study the ethnomathematics of Kudus culture and mathematical problem-solving abilities in flat shapes in order to generate innovative findings in mathematics education.